Alternative postharvest technologies for the maintenance of ‘Parthenon’ broccoli quality during export and domestic marketing. - De Beer, Tarryn (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.